Opportunities to improve the immune status of broiler chickens - Karakolev, R; Koynarski, Ts; Sotirov, L; Petrova, R; Petrova-Tsenin, P (Journal of the Hellenic Veterinary Medical Society, 2024)
Since 2006, the European Community has banned the use of nutritional antibiotics as growth promoters in livestock husbandry. The utilization of modern poultry production systems with a high degree of concentration and automation has resulted in the health status of sensitive poultry strains and hybrids. Some humoral indicators of natural immunity in broiler chickens from the ROSS 308 hybrid and growing broiler breeders were studied. The experiment was conducted in control and experimental herds raised under the same production conditions. The experimental herds were reared without the use of antibiotics but were treated with the immunomodulator Avigen. The serum lysozyme concentrations, the alternative pathway of complement activity (APCA), and concentrations of IFN γ, IL-2, and IL-6 of broilers treated with Avigen significantly exceeded the values in the control birds. The same tendency is observed among the growing broiler breeders. Serum IgY concentrations show a significant difference in growing broiler breeders but not in broilers. Based on the obtained data, the treatment with the immunomodulator Avigen increases the natural resistance of birds, which allows them to be raised without the use of antibiotics in production conditions.